Highly efficient and stable AgI–CdO nanocomposites for photocatalytic and antibacterial activity. Issue 8 (9th February 2023) - Warshagha, Murad Z. A.; Muneer, M.; Althagafi, Ismail I.; Ahmed, Saleh A.
Abstract : For the last several decades, semiconducting materials and nanocomposites have received a lot of interest in generating highly efficient photocatalysts to destroy organic pollutants and eradicate bacteria. Abstract : For the last several decades, semiconducting materials and nanocomposites have received a lot of interest in generating highly efficient photocatalysts to destroy organic pollutants and eradicate bacteria. This study uses a simple deposition and precipitation approach at ambient temperature to create a unique and efficient AgI–CdO heterojunction. DRS, IR, SEM, EDS, XRD, EIS, and TEM were utilized to identify the material. SEM and TEM investigation depict the completely spherical, hexagonal forms and zigzag cubes for synthesized AgI–CdO. The EDX spectra reveal the presence of Ag, I, Cd, and O elements without impurity peaks showing that the prepared samples are highly pure. The activity of the synthesized materials was tested by degrading two different chromophoric dyes and a drug derivative (paracetamol) in an aqueous suspension under visible light. In addition, the activity of the most active catalyst was compared with Degussa P25, Fenton's reagent, and under sunlight for degradation of MB and RhB under similar conditions. Photolysis of paracetamol was also looked at using HPLC to identify intermediates formed in the photo-oxidation process. In addition, antibacterial activity was also investigated with the synthesized CdO–AgI nanocomposite in vitro against human pathogenic bacterial strains and compared with that of pure materials like AgI and standard ampicillin. The results showed excellent activity with the composite material, which could be due to the higher surface areas and the interactions between AgI and CdO nanoparticles. Quenching investigations revealed O2 ˙ − and holes are principal reactive species. A viable photocatalytic degradation mechanism for organic pollutant elimination over the AgI–CdO nanocomposite has been sketched out based on the obtained results.